Perception of online education during COVID-19: Online Photovoice (OPV) and ecological systems theory - Tanhan, Ahmet; Taş, Besra; Ağılkaya Şahin, Zuhal; Hayden, Seth C. W.; Korkmaz, Ozan; Gürsu, Orhan; Taş, Besra (Routledge Journals, 2023)
In this research, we used Community-Based Participatory Research, Ecological Systems Theory and active interdisciplinary social advocacy perspectives as part of our theoretical framework. Our sample consisted of 530 counselling undergraduate students with 481 consenting to participate by sharing the most important main facilitators and barriers for their online or distance education during COVID-19 pandemic. We used Online Photovoice methodology to get the students lived experiences focusing on their counselling major and Online Interpretative Phenomenological Analysis to analyse shared experiences. Thirteen main facilitators emerged (e.g. The contribution of technology in distance education, 22%; computer, PC: Technological tools, 18%; internet, 14%) and 22 main barrier themes emerged (e.g. lack of technological tools and related knowledge, 16%; transition to distance education, 13%; emotions that are difficult to cope with, 12%). We also examined how participants attribute these facilitator and barrier themes to Ecological Systems Theory levels.
Keywords: Counselling education; Community-Based Participatory Research (CBPR); Pandemic; Online and distance education; Online Photovoice (OPV)